The effect of celastrol on the ocular hypertension-induced degeneration of retinal ganglion cells. (23rd March 2018) - Gu, Lei; Kwong, Jacky M.K.; Yadegari, Daniel; Yu, Fei; Caprioli, Joseph; Piri, Natik
Highlights: The present study evaluates the effect of celastrol on the survival of RGCs injured by ocular hypertension. Intraocular pressure (IOP) elevation resulted in approximately 23% of RGCs loss. Reduction in RGC numbers was observed in all four retinal quadrants: 30% in superior, 17% in inferior, 11% in nasal and 35% in temporal regions. Celastrol treatment stimulated RGC survival by an average of 24% in the entire retina compared to the vehicle-treated group. Abstract: Celastrol, a quinine methide triterpene extracted from the perennial vine Tripterygium wilfordii, has been identified as a neuroprotective agent in various models of neurodegenerative disorders. We have reported earlier that systemic and intravitreal administration of celastrol stimulate the survival of retinal ganglion cells (RGCs) injured by optic nerve crush (ONC) and that mechanisms underlying celastrol׳s RGC protection may be associated with inhibition of TNF-alpha-mediated cell death. The present study evaluates the effect of celastrol on the survival of RGCs injured by ocular hypertension. Intraocular pressure (IOP) elevation resulted in approximately 23% of RGCs loss. Reduction in RGC numbers was observed in all four retinal quadrants: 30% in superior, 17% in inferior, 11% in nasal and 35% in temporal regions. Celastrol (1 mg/kg) or vehicle (DMSO) was administered three times per week by intraperitoneal injection, starting on the day of laser photocoagulation of the TM and continued for the entire duration of the experiment (5 weeks). Celastrol treatment stimulated RGC survival by an average of 24% in the entire retina compared to the vehicle-treated group. RGC numbers were increased in all four quadrants: approximately 40%, 17%, 15% and 30% more RGCs were counted in the superior, inferior, nasal and temporal regions, respectively. The average RGC numbers for the entire retinas of the celastrol/IOP group were only ∼5% and 10% lower than that in vehicle- or celastrol-injected animals with normal IOP, respectively. Our data indicate a significant celastrol-mediated neuroprotection against elevated IOP-induced injury.